Challenges Faced by Multi-Campus Institutions with Online Teaching during the COVID-19 Lockdown - Covanni Hohls-du Preez; Ben Marx (MDPI AG, 2023)
In December 2019, the COVID-19 virus was first detected in Wuhan, Hebei Province, China. On 11 March 2020, the World Health Organisation declared the COVID-19 virus a world pandemic. Even though the physical closure of tertiary institutions had proven to be an effective strategy in breaking the transmission chain in the pandemic, the closure still had various negative effects on students' academic endeavours. In an attempt to keep the disruption of studies to a minimum, higher education institutions across the world implemented online learning programmes by converting face-to-face programmes, thereby creating various challenges for students and lecturers on different levels. The purpose of this article was to determine how challenges faced by multi-campus universities in South Africa during this time would compare to challenges faced by other countries. This study focused on two specific multi-campus universities in South Africa with similar student bodies that offered various accounting courses on different campuses. These courses ranged from diplomas to CTA degrees.